Moral Standards In Proverbs: An Axiological Analysis Of English And Uzbek Paremiology - Makhkamova Muniskhon (International Journal Of Literature And Languages, 2025)
The axiological aspect of Uzbek and English proverbs is examined in this article, with special focus on how moral standards and value judgments are represented linguistically in paremiological units. The study views proverbs as culturally ingrained linguistic structures that combine semantic meaning with evaluative orientation, drawing on the theoretical frameworks of comparative paremiology and axiological linguistics. A corpus of proverbs expressing moral judgment in both languages is subjected to a qualitative semantic-pragmatic analysis. Honesty, diligence, patience, humility, generosity, justice, and social duty are among the fundamental moral categories identified by the research, which also examines their pragmatic role in discourse and metaphorical realization. The results demonstrate the coexistence of cultural-specific evaluation patterns and universal moral norms. While Uzbek proverbs promote collectivism, communal harmony, religious-ethical principles, and respect for social hierarchy, English proverbs typically emphasize individual responsibility, pragmatism, and self-control. The work advances the fields of axiological paremiology and international linguistics by showing how proverbs act as normative linguistic processes that control conduct, communicate cultural knowledge, and uphold collective value systems.